Management of External Parasites with Forced-Use Dust Bags - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS)
Over the past 13 years IFAS entomologists have been investigating various methods of controlling external parasites on cattle. One technique, forced-use dust bags, has proven to be the best technique available to Florida cattlemen. This document is ENY-281 (first published as LPP No. 12, May 1980), one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date September 1996. Revised March 2006.